Successful Management of Diabetic Foot Ulcer Complicated by Osteomyelitis Using Platelet-rich Plasma Therapy: A Case Report - Mehrizi, Saeed Abouei; Heidari, Nazila; Heidari, Amirhossein; Ghane, Yekta; Nilforoushzadeh, Mohammad Ali (Current Stem Cell Research & Therapy, 2025)
<span class=
Keywords: platelet-rich plasma